Математическое обеспечение численного анализа импульсного возбуждения линейного электродвигателя с двухпараметрической функцией магнитного потокосцепления - Милых, Владимир Иванович; Ткаченко, Сергей Валериевич; Milykh, V.; Tkachenko, S. (Кременцугский национальный университет им. М. Остроградского, 2010)
Рассматривается одна из проблем численного расчета рабочего режима линейного электродвигателя при его импульсном возбуждении. Для ее решения представлен принцип определения частных производных нелинейной функции магнитного потокосцепления его обмоток по току и взаимному смещению реактора и якоря.

One of problems of numeral calculation of operating condition of linear electric motor is considered at his impulsive excitation. For its decision the determination principle of particular derivative of non-linear function of magnetic flux linkage of his winding on a current and mutual displacement of reactor and armature is presented
Mathematical providing of numerical analysis of impulsive excitation of linear electric motor with two-parameter function of magnetic flux linkage
Keywords: переходный процесс; обеспечение численного расчета; частные производные; transitional process; providing of numeral calculation; particular derivative; реактор